Isolation and identification of a novel canine parvovirus type 2c strain in domestic cats in Dalian, China - Jing, Zheng; Ji, Peng; Wei, Yanquan; Hao, Fuxing; Wei, Yanming (Frontiers in Veterinary Science, 2022)
Canine parvovirus (CPV) and feline panleukopenia virus (FPV) are highly contagious and cause severe enteric diseases, with high mortality rates in dogs and cats. In the present study, we isolated and identified a novel CPV-2c strain (FPV-DL04 strain) from 18 cats with gastroenteritis symptoms and a positive parvovirus PCR test result in Dalian, China. Molecular characterization, sequence analysis, and phylogeny determination were performed on the VP2 gene of this strain. The results showed that the FPV-DL04 strain had 99.4% homology with the CPV-2c CN/HN1708 strain, and both strains had S297A and A300G key mutation sites. Interestingly, we also found that the DL04 strain has a A5G mutation site, but no F267Y and Y324I mutation sites. This study provided new important findings regarding the evolution of parvovirus infection in domestic cats in China.